Foreign capital and industrialization in Malaysia - "Rasiah, Rajah" (New York, 1995)
This book examines foreign capital's role in stimulating industrialization. Using both conventional and unconventional approaches, the author finds foreign capital to have played a positive role in Malaysia's industrialization. The branch- and industry-level analyses show generally strong pecuniary effects by foreign capital. Local-dominated branches and industries, however, show strong linkages with the domestic economy. The firm-level analysis tends to reveal strong technological spillovers from foreign capital. The book closes with regulatory prescriptions to enhance positive spillovers.
Keywords: Malaysia-manufactures-foreign ownership